Crosstalk of MicroRNAs and Oxidative Stress in the Pathogenesis of Cancer. (28th April 2020) - Lu, Can; Zhou, Danting; Wang, Qiang; Liu, Wenliang; Yu, Fenglei; Wu, Fang; Chen, Chen
Abstract : Oxidative stress refers to an imbalance between reactive oxygen species (ROS) generation and body's capability to detoxify the reactive mediators or to fix the relating damage. MicroRNAs are considered to be important mediators that play essential roles in the regulation of diverse aspects of carcinogenesis. Growing studies have demonstrated that the ROS can regulate microRNA biogenesis and expression mainly through modulating biogenesis course, transcription factors, and epigenetic changes. On the other hand, microRNAs may in turn modulate the redox signaling pathways, altering their integrity, stability, and functionality, thus contributing to the pathogenesis of multiple diseases. Both ROS and microRNAs have been identified to be important regulators and potential therapeutic targets in cancers. However, the information about the interplay between oxidative stress and microRNA regulation is still limited. The present review is aimed at summarizing the current understanding of molecular crosstalk between microRNAs and the generation of ROS in the pathogenesis of cancer.